2009
DOI: 10.1186/1465-9921-10-92
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression patterns in the post-pneumonectomy lung of adult mice

Abstract: BackgroundAdult mice have a remarkable capacity to regenerate functional alveoli following either lung resection or injury that exceeds the regenerative capacity observed in larger adult mammals. The molecular basis for this unique capability in mice is largely unknown. We examined the transcriptomic responses to single lung pneumonectomy in adult mice in order to elucidate prospective molecular signaling mechanisms used in this species during lung regeneration.MethodsUnilateral left pneumonectomy or sham thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
5
21
1
Order By: Relevance
“…In the mutant mesenchyme, transgelin (Tagln)-positive smooth muscle cells were restricted to the proximal airways as in the wildtype. It has recently been shown that expression of S100 calcium binding protein A4 (S100a4) marks fibroblasts that are highly proliferative and express low levels of extracellular matrix proteins indicating the precursor character of these cells [28][29][30]. We found that in E14.5 wildtype lungs all mesenchymal cells that were positive for S100a4 also incorporated BrdU confirming the proliferative character of this cell type ( Figure S3).…”
Section: Author Summarysupporting
confidence: 65%
“…In the mutant mesenchyme, transgelin (Tagln)-positive smooth muscle cells were restricted to the proximal airways as in the wildtype. It has recently been shown that expression of S100 calcium binding protein A4 (S100a4) marks fibroblasts that are highly proliferative and express low levels of extracellular matrix proteins indicating the precursor character of these cells [28][29][30]. We found that in E14.5 wildtype lungs all mesenchymal cells that were positive for S100a4 also incorporated BrdU confirming the proliferative character of this cell type ( Figure S3).…”
Section: Author Summarysupporting
confidence: 65%
“…Differentiation to lung epithelial cells was assessed by incubation of L-MSCs in small airway growth media (SAGM with SingleQuots) containing rhEGF (0.5 ng/mL) for 8 days, and measurement of Aqp5, Ttf-1, proSPC (Sftpc), and CCSP (Scgb1A1) mRNA expression. qPCR was performed according to past descriptions from our laboratory [32,37] using housekeeping genes (average of Hrtp1, GusB, and GADPH) for normalization of mRNA. Details of qPCR methodology are provided in the Supplementary Methods.…”
Section: Differentiation Assays Of L-mscsmentioning
confidence: 99%
“…This is particularly applicable and appropriate to our individual time point datasets in which we have only one paired array set for each time point and has been described by our laboratory in previous analyses [19]. By definition, Sscore is related to P-value by an exponential relation, and a value of three corresponds to a P-value of 0.003 [24,27].…”
Section: Microarray Analysismentioning
confidence: 99%
“…As is seen with many mammals during periods of high somatic growth [1,17], young adult mice are capable of extensive lung regeneration after unilateral pneumonectomy [18,19]. During postpneumonectomy lung regeneration, cell proliferation occurs throughout the lung parenchyma in mesenchymal, endothelial, and epithelial compartments, as demonstrated by DNA labeling studies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation